An Analysis on Decline and Achievement of the Mughal In India: Understanding Trading Patterns in the Mughal Empire (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This paper identifies the absence of bothsub-continentally oriented histories which knit together the land and seatrades, and convincing explanations of the persistence of the Indo-CentralAsian trade (for example) despite the growing Indo-European trade from theseventeenth-century. The customs-union model usefully approximates thistrading-situation (i.e. the Europeans were given a privileged trading positionby the Mughals vis-à-vis the Central Asians). It is used to structure theinvestigation and provide suitable explanatory hypotheses, as it suggests theseparation of the likely creative and divertive effects of such privilegedrelations. Two tradable (and related industries) are examined. Thetextile-industry demonstrates the possibility for trade-creation (i.e. due tosubstitution between otherwise regionally-specialized production-centres as inGujarat, and the utilization of spare capacity as in Bengal); it is not,however, possible to comment on the extent to which trade-creation took place.The horse-trade persisted because of limited trade-diversion. This was in turnthe consequence of the absence of a European supply of horses, on the one hand,and the continued/unchanging geographical comparative advantage and demandconditions in the Mughal Empire, on the other. The necessary extensions to themodel and analysis – for a complete understanding of sub-continental tradingpatterns – are noted (e.g. extending geographical and chronological scope,investigating private trading, and introducing balance of payments issues).